Forests in Our Changing World New Principles for Conservation and Management - Landsberg, Joe; Waring, Richard (Island Press/Center for Resource Economics : Imprint: Island Press, 2014)
Scientists tell us that climate change is upon us and the physical world is changing quickly with serious implications for biodiversity and human well-being. Forests cover vast regions of the globe and serve as a first line of defense against the worst effects of climate change, but only if we keep them healthy and resilient. Forests in Our Changing World tells us how to do that. Authors Joe Landsberg and Richard Waring present an overview of forests around the globe, describing basic precepts of forest ecology and physiology and how forests will change as earth's climate warms. Drawing on years of research and teaching, they discuss the values and uses of both natural and plantation-based forests. In easy-to-understand terms, they describe the ecosystem services forests provide, such as clean water and wildlife habitat, present economic concepts important to the management and policy decisions that affect forests, and introduce the use of growth-and-yield models and remote-sensing technology that provide the data behind those decisions. This book is a useful guide for undergraduates as well as managers, administrators, and policy makers in environmental organizations and government agencies looking for a clear overview of basic forest processes and pragmatic suggestions for protecting the health of forests.